2018
DOI: 10.1002/ejoc.201801393
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Benzothiazolone Derivatives by a Domino Reaction of Disulfide and COS under Mild Conditions

Abstract: Carbonyl sulfide (COS), whose molecular structure is similar to CO2 and CS2, could be used as a better alternative carbonyl reagent due to its high chemical activity. However, the unfriendly by‐product H2S would be generated when COS is used as a carbonyl reagent in the carbonylation reaction. In this report, the odorless and stable disulfide was used to replace the traditional foul smelling and unstable o‐aminobenzenethiol to react with COS for preparing benzothiazolone derivatives in excellent yield, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…One of the key steps in the synthesis of benzothiazole from disulfide is the cleavage of S–S bond. It is found that the S–S bond can be cleaved by free radical reagents, 25,26 metal catalysts, 27,28 nucleophilic reagents, 23,29 reducing reagents, 30–32 thiol-disulfide exchange reaction 33–35 and the disulfide-metal sulfide dynamic interchange reaction. 36,37 Therefore, 2-unsubstituted benzothiazole is synthesized by reductive cyclization of disulfide and CO 2 , a crucial reducing reagent which could reduce CO 2 and the S–S bond of disulfide is required (Scheme 1, route b).…”
Section: Introductionmentioning
confidence: 99%
“…One of the key steps in the synthesis of benzothiazole from disulfide is the cleavage of S–S bond. It is found that the S–S bond can be cleaved by free radical reagents, 25,26 metal catalysts, 27,28 nucleophilic reagents, 23,29 reducing reagents, 30–32 thiol-disulfide exchange reaction 33–35 and the disulfide-metal sulfide dynamic interchange reaction. 36,37 Therefore, 2-unsubstituted benzothiazole is synthesized by reductive cyclization of disulfide and CO 2 , a crucial reducing reagent which could reduce CO 2 and the S–S bond of disulfide is required (Scheme 1, route b).…”
Section: Introductionmentioning
confidence: 99%
“…One of common method for 3‐alkyl‐2(3H)‐benzothiazolones is the use of toxic and bad‐smell ortho‐ amino/ ortho‐N‐ substituted amino thiophenols and carbonyl reagents to undergo cyclocarbonylation (Scheme 1, previous work a) [4] . Reported carbonyl reagents for this kind of transformation include highly toxic phosgene, [4a] toxic triphosgene, [4b] carbon monoxide (CO) under high pressure, [4c,d] carbon dioxide (CO 2 ) under high pressure [4e] or high temperature, [4f] bad‐smell and flammable gas carbonyl sulfide, [4g,h] urea requiring a high temperature of 140 °C, [4i,j] isocyanate, [4k] 2‐phenoxycarbonyl‐4,5‐dichloropyridazin‐3(2H)‐one [4l] as well as carbonyl difluoride [4m] . Another synthetic method for 3‐alkyl‐2(3H)‐benzothiazolones is from o ‐haloanilines, sulfur reagents, and carbonyl reagents [5] .…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al developed a straightforward synthesis of benzothiazolone derivatives via a tandem coupling reaction between aromatic disulfides and COS in the presence of NaOH at room temperature [Eq. (52)].…”
Section: Condensation Of 2‐aminothiophenol Disulfides With Differementioning
confidence: 99%